ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN DAN EARNING PER SHARE SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX (JII) - Muwidha Muwidha; Mahmudatul Himma; Riwajanti Riwajanti (Politeknik Negeri Malang, 2018)
This study aims to analyze the role of Dividend Policy and Stock Performance in moderating Profitability within creating Company Value. The population during the analysis period was 30 companies. After sampling with a purposive approach obtained a sample of 17 companies. Descriptively known value The profitability proxied by the value of ROA of 38.72% while the value of the company proxied by Tobin’s Q is averaging 1.02. In theory ROA has a strong positive effect on Company Value. The findings in the study indicate that ROA does have a positive effect but only 6.6% is significant. This result explains that investors still believe that profit is a real signal of the expected profit. These two conditions relate that investors in the sharia-based capital market are not fair in valuing companies. Because profitability is not a concern even the dividend payment policy is not considered capable of giving a signal in appreciating the company, but net income in real terms is precisely what is expected.